Politik Hukum: Sertipikat Elektronik pada Sertipikat Ganda - Lambu, Asry Mora; Audrey, Jeniffer Clarrisa; Meha, Megawati H.M.; Sutanto, Michelle Alycia; Paputungan, Pingkan Ester Amelia (JURNAL MINUTA, 2025)
The use of electronic certificates in land ownership in the digital era offers a modern solution, but also faces challenges in handling cases of dual certificates. This article examines the process of proving electronic certificates when there is a dispute over claims of dual ownership, as well as how legal protection is provided to ensure the validity and security of electronic land certificates. Through a legal analysis, this article discusses verification mechanisms that can strengthen the authenticity of electronic certificates, including the use of technologies such as blockchain as an effort to increase transparency and public trust. In addition, this article also evaluates the guarantee of protection provided for electronic land certificates, which include the arrangement of unique codes, QR codes, and limited access policies on certain applications such as Sentuh Tanahku which can only be accessed by related parties, such as the government, Notaries, and PPAT. Obstacles in proving the legality of electronic certificates in court are also discussed, especially regarding the validity of data and the recognition of electronic certificates as valid evidence. By identifying the obstacles and opportunities in the implementation of electronic certificates, this article provides insight into the steps needed so that electronic certificates can become a valid and trusted instrument of proof of land ownership in resolving dual certificate conflicts. Keywords: Electronic Land Certificate, Overlapping Certificate, Evidence, Legal Certainty